Impedance spectroscopy studies of poly (methyl methacrylate)-lithium salts polymer electrolyte systems - Othman, L.; Chew, K. W.; Osman, Z. (SPRINGER HEIDELBERG, 2007)
In the present work, five systems of samples have been prepared by the solution casting technique. These are the plasticized poly(methyl methacrylate) (PMMA-EC) system, the LiCF3SO3 salted-poly(methyl methacrylate) (PMMA-LiCF3SO3) system, the LiBF4 salted-poly(methyl methacrylate) (PMMA-LiBF4) System, the LiCF3SO3 salted-poly(methyl methacrylate) containing a fixed amount of plasticizer ([PMMA-EC]-LiCF3SO3) system, and the LiBF4 salted-poly(methyl methacrylate) containing a fixed amount of plasticizer ([PMMA-EC]LiBF4) system. The conductivities of the films from each system are characterized by impedance spectroscopy. The room temperature conductivity in the pure PMMA sample and (PMMA-EC system is 8.57x 10(-13) and 2.71 x 10(-11) S cm respectively. The room conductivity for the highest conducting sample in the (PNINIA-LiCF3SO3), (PMMA-LiBF4), ([PMMA-EC]-LiCF(3)SO3 and ([PMMA-EC]LiBF4) systems is 3.97 x 10(-6), 3.66 x 10(-7), 3.40 x 10(-5), and 4.07 x 10(-7) S cm(-1), respectively. The increase in conductivity is due to the increase in number of mobile ions, and decrease in conductivity is attributed to ion association. The increase and decrease in the number of ions can be implied from the dielectric constant, epsilon(r)-frequency plots. The conductivity-temperature studies are carried out in the temperature range between 303 and 373 K. The results show that the conductivity is increased when the temperature is increased and obeys Arrhenius rule. The plots of loss tangent against temperature at a fixed frequency have showed a peak at 333 K for the ([PMMA-EC]-LiBF4) system and a peak at 363 K for the ([PMM-EC]-LiCF3SO3) system. This peak could be attributed to P-relaxation, as the measurements were not carried out up to glass transition temperature, Tg. It may be inferred that the plasticizer EC has dissociated more LiCF3SO3 than LiBF4 and shifted the loss tangent peak to a higher temperature.